Factors associated with involuntary admissions among patients with substance use disorders and comorbidity: a cross-sectional study - Opsal Anne; Kristensen Øistein; Larsen Tor K; Syversen Gro; Rudshaug Bakke Elise; Gerdner Arne; Clausen Thomas (BMC, 2013)
Abstract Background To investigate factors associated with involuntary admissions to hospital pursuant to a social services act of patients with substance use disorder by comparing the socio-demographic characteristics, substance use, and psychiatric comorbidities with voluntarily admitted patients. Methods This cross-sectional study compared two groups admitted to combined substance use disorder and psychiatry wards. Sixty-five patients were involuntarily admitted pursuant to the Social Services Act and 137 were voluntarily admitted. The International Classification of Diseases and Related Health Problems was used for diagnostic purposes regarding substance use disorders, type and severity of psychiatric problems, and level of functioning. Socio-demographic variables were measured using the European Addiction Severity Index, and the Symptom Checklist-90-R instruments were used to evaluate the range of psychological problems and psychopathological symptoms. Logistic regression was performed to investigate the relationship between involuntary admissions and patients characteristics. Results Patients who had been involuntarily admitted were more likely to be females, had utilized public welfare services more often, presented more severe substance use patterns, and had a history of more frequent visits to physicians for somatic complaints in the last 6 months, they also had fewer comorbid mental disorders. Still, considerable burdens of comorbid substance use disorders and mental disorders were observed both among involuntary and voluntary admitted patients. Conclusions More attention is required for involuntarily admitted patients in order to meet the needs associated with complex and mixed disorders. In addition, treatment centers should offer diagnostic options and therapy regarding substance use, psychiatric and somatic disorders.